Roles of the state in emerging process of innovation system - Hung, Nguyen Vo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The concepts of innovation were developed from studies generated from context of developed nations. The direct and mechanical application of this approach for developing countries could lead to wrong judgments. In developing countries with open economy, a type of innovation system is on emerging process where the main interactions develop between enterprises under intervention of foreign factors and limited roles of science and technology (S&T) agencies. This development should be assessed as quite natural feature for their context. The incompleteness of the system should not be taken into consideration as a weak point. Learning and scaling-up of innovations are found more important than R&D is itself. The role of the State in this process should be also re-considered. Policies should pay attention to institutions to support learning mechanisms where activities of technological promotion should be mobilized. The establishment of background for development of innovation system may be more important than segmented measures to target narrowly some beneficiaries. Code: 14061202